Development of virtual assembly layout with modeling languages approach and simulation using Delmia™ Quest® - M., Norhidayah; H. M., Yupiter; J., Roseleena; A., Shaharudin; Adesta, Erry Yulian Triblas (IIUM Press, 2011)
The paper presented the development of virtual layout model with modeling languages approach. This research also explores the flexibility of the model configurations through the development process of database for storing and representing the virtual model. The concept and mechanisms of database development involves the use of eXtensible Markup Language (XML). The objectives of the research are therefore to obtain a basic understanding on how these modeling languages are used to develop virtual model, representing the simulation by using Delmia™ QUEST® and develop a database for share, store and future usage. Therefore, the generated simulation presents the feasibility of interchanging models using modeling language approach as an intermediate representation and provides an opportunity to improve simulation quality.